TRANSFORMASI PEDAGOGI EKONOMI DI ERA DIGITAL TERHADAP EFEKTIVITAS KURIKULUM DAN KREATIVITAS GURU DALAM MENINGKATKAN HASIL BELAJAR EKONOMI SISWA GEN Z DAN GEN ALPHA - Siti Nur Dianasyah (Universitas Nias Raya, 2026)
The economic learning outcomes of digital generation students (Gen Z and Alpha) are influenced by curriculum effectiveness and teacher creativity. There are differences between conventional economics teaching approaches and digital student teaching approaches that require engagement and technology. This causal associative quantitative study involved 370 Indonesian high school students selected through stratified random sampling. Teacher creativity (X1) and curriculum effectiveness (X2), which have been validated and validated respectively, were collected using a Likert scale questionnaire. Standardized tests were used to measure economic learning outcomes (Y). The results of multiple linear regression analysis showed that economic learning outcomes were positively and significantly affected by curriculum effectiveness (F = 88.910, p < 0.01); teacher creativity was positively and significantly affected by economic learning outcomes (F = 0.480, p < 0.01). These results suggest that more adaptive curriculum reform and teacher professional development are essential to enhance student creativity and provide Gen Z and Alpha students with an understanding of modern economics.